Efektivitas Pemberian Bantal Anti Dekubitus Pada Pasien Bedrest : Case Report - Anzalna Risma Fattah, Raden Ajeng; Budiati Sri Hidayati, Ari (Jurnal Syntax Fusion, 2023)
After using an anti-decubitus pillow, the score on the Braden scale obtained was 15, indicating a low risk of pressure sores. For 5 days, the application of the oblique position with an anti-decubitus pillow was carried out in patients with a medical diagnosis of non-hemorrhagic stroke. This study concluded that there was a change of 80% after being given an oblique position with an anti-decubitus pillow. Purpose: This study aims to analyze the establishment of pressure painful prevention pillows that can be used by long-bed rest patients to prevent pressure wounds at PKU Muhammadiyah Yogyakarta Hospital. Method: The method in this study uses a case report. The design in this study used descriptive based on the provision of anti-decubitus pillows to reduce pressure sores. Results: The outcomes of this study proved that giving anti-decubitus pillows was effective in reducing the risk of pressure wounds in bedrest patients. Suggestion: Bedrest patients can apply the position of using pillows effectively to reduce pressure sores on bedrest patients.